2016
DOI: 10.1182/blood-2015-07-661983
|View full text |Cite
|
Sign up to set email alerts
|

Presence of atypical thrombopoietin receptor (MPL) mutations in triple-negative essential thrombocythemia patients

Abstract: Key Points• Enrichment of atypical MPL mutations in essential thrombocythemia.• MPLS204P and MPLY591N mutants are weak gain-offunction mutants.Mutations in signaling molecules of the cytokine receptor axis play a central role in myeloproliferative neoplasm (MPN) pathogenesis. Polycythemia vera is mainly related to JAK2 mutations, whereas a wider mutational spectrum is detected in essential thrombocythemia (ET) with mutations in JAK2, the thrombopoietin (TPO) receptor (MPL), and the calreticulin (CALR) genes. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
139
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(145 citation statements)
references
References 49 publications
3
139
2
1
Order By: Relevance
“…These mutations were found to have a weak gain-of-function effect, either with a degree of thrombopoietin-independent growth or signaling, or thrombopoietin hypersensitivity. 36,37 Mutations in calreticulin (CALR) are also found in approximately 25-35% of patients with ET and 35-40% of those with MF ( Figure 2A). These are exclusively insertions/deletions (most commonly a 52 base pair deletion or 5 base pair insertion) in the final exon ( Figure 1B), and in all cases these result in a 1 base pair shift in the reading frame.…”
Section: Mutations In Mpl and Calrmentioning
confidence: 99%
“…These mutations were found to have a weak gain-of-function effect, either with a degree of thrombopoietin-independent growth or signaling, or thrombopoietin hypersensitivity. 36,37 Mutations in calreticulin (CALR) are also found in approximately 25-35% of patients with ET and 35-40% of those with MF ( Figure 2A). These are exclusively insertions/deletions (most commonly a 52 base pair deletion or 5 base pair insertion) in the final exon ( Figure 1B), and in all cases these result in a 1 base pair shift in the reading frame.…”
Section: Mutations In Mpl and Calrmentioning
confidence: 99%
“…Two recent studies have indeed shown that a few triplenegative patients carry activating mutations of MPL outside exon 10, and that these noncanonical mutations may be either inherited or somatically acquired. 23,24 One study has also shown that some patients carry noncanonical, activating mutations of JAK2, which appear to be germ line in most instances. 23 Finally, some patients have evidence of polyclonal hematopoiesis, and most likely do not have a true MPN.…”
Section: How We Diagnose Etmentioning
confidence: 99%
“…Hereditary thrombocytosis may be associated with germ line mutations of THPO, the thrombopoietin gene, 63,64 or MPL, the thrombopoietin receptor gene. 23,24,65 Recent reports have described cases of hereditary thrombocytosis associated with noncanonical germ line mutations of JAK2. 23,[66][67][68][69] In familial ET, JAK2 (V617F) is always a somatically acquired event, as in the familial tree reported in Figure 2.…”
Section: Distinguishing Familial Et From Hereditary Thrombocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Recent work suggests that these patients may either have hereditary thrombocytosis or harbor as yet less well-described mutations in MPL or JAK2. [6][7][8] Patients with ET are commonly asymptomatic, but may throughout the course of the disease develop microvascular (headache, dizziness, erythromelalgia), thromboembolic or hemorrhagic complications. Disease progression to myelofibrosis (MF), termed post-ET myelofibrosis (PET-MF), in ET is thought to be uncommon particularly when strict interpretation of the WHO diagnostic criteria is applied, making the distinction between the so-called true ET and prefibrotic MF.…”
mentioning
confidence: 99%